Drivers of Conflict in Urban Infrastructure: Case Study of the New Yogyakarta Airport - Fitriantoro, Muchamad Imam (UI Scholars Hub, 2020)
The study discusses the drivers of conflict in the construction of Yogyakarta International Airport (YIA) in Temon, Kulon Progo, using a politico-economic framework. This research employs the theory of land-based elite domination of urban growth machines and theories that explain the drivers of conflicts caused by construction and development of infrastructure. The findings of this study show that the conflict was driven by disagreements on land resource that emerged from the government’s ambition to respond to the pressure to transform the rural lands in the region into an urban area under the concepts of aerotropolis and MICE. The pressure came from the interests of local and national elite groups, which complemented the extant problem of domination of land ownership by the local political elites of Daerah Istimewa Yogyakarta. Thus, the conflict was related to not only the development of infrastructure but also a land conflict that arose from urban development policies. The other drivers of the conflict include poor governance of the project and social factors.